SISTEM INFORMASI AUTOMATIC TANK GAUGE PADA PT PERTAMINA PATRA NIAGA INTEGRATED TERMINAL PALEMBANG - Muhammad Fakhri Azfar; Gina Agiyani (Jurnal Riset Sistem Informasi, 2026)
Information systems play a vital role in supporting efficiency and accuracy in operational management with in the oil and gas industry. PT Pertamina Patra Niaga Integrated Terminal Palembang requires a system capable of ensuring real-time accuracy of fuel volume and quality data. This study aims to design an Automatic Tank Gauge (ATG) information system integrated with the monitoring and inventory control processes of fuel storage at the terminal. The research method involves system requirements analysis, field data collection, and the design of a system model based on ATG sensor technology connected to the company’s information system. The design results show that the ATG information system can provide automatic and accurate data on fuel volume, temperature, and density, thereby minimizing manual recording errors and supporting operational transparency. The implementation of this system is expected to improve inventory control effectiveness, accelerate decision-making, and strengthen overall terminal fuel management governance.